An efficient photoanode for dye sensitized solar cells using naturally derived S/TiO2 nanoparticles. (9th March 2017) - Arunmetha, S; Rajendran, V; Vinoth, M; Karthik, A; Srither, S R; Srither Panday, M; Nithyavathy, N; Manivasakan, P; Maaza, M
Abstract: Natural mineral rutile sand is used for preparing titania (TiO2 ) nanoparticles employing a cost-effective simple chemical method and mass production technology. Further the sulfur doped (S/TiO2 ) and pure TiO2 are produced from chemical precursor also. Different techniques are used to analyse the effect of sulfur dopant like x-ray diffraction, Fourier-transform infrared spectroscopy, Raman spectroscopy, x-ray photoelectrons spectroscopy, ultraviolet–visible spectra, photoluminescence, Brunauer–Emmett–Teller analyser, field emission scanning electron microscopy with energy-dispersive x-ray analysis, and high-resolution transmission electron microscopy. Under visible light, a useful procedure is followed on the sulfur-doped samples preparation, enhancing the charge carrier recombination, and reducing crystallite size. In the improvement of the efficiency of dye-sensitized solar cells, this dopant could open up vast opportunities; consequently, our work is extended to apply these prepared samples in standard dye-sensitized solar cells. The photoanode of dye-sensitized solar cells are made up of these prepared materials (S-doped TiO2 and pure TiO2 ) and compared with both commercial TiO2 (P-25) powder, as well as commercially available paste (Dyesol). The S/TiO2 nanoparticles on dye-sensitized solar cells exhibit enhanced ultra-violet visible light absorbance with increased photogenerated electrons and holes meanwhile reduce the recombination rate of charge carriers in dye-sensitized solar cells. Further, the overall power-conversion efficiency ( η ) and external quantum efficiency of the S/TiO2 cells ( η   =  4.32% and EQE  =  32%) is two times higher than that of pure TiO2 cells ( η   =  2.75% and EQE  =  16%).